2015
DOI: 10.1038/srep14808
|View full text |Cite
|
Sign up to set email alerts
|

Microscopic basis for the band engineering of Mo1−xWxS2-based heterojunction

Abstract: Transition-metal dichalcogenide layered materials, consisting of a transition-metal atomic layer sandwiched by two chalcogen atomic layers, have been attracting considerable attention because of their desirable physical properties for semiconductor devices, and a wide variety of pn junctions, which are essential building blocks for electronic and optoelectronic devices, have been realized using these atomically thin structures. Engineering the electronic/optical properties of semiconductors by using such heter… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

5
69
0

Year Published

2016
2016
2019
2019

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 53 publications
(74 citation statements)
references
References 28 publications
(44 reference statements)
5
69
0
Order By: Relevance
“…As a result, a number of successful strategies for doping 2D materials have been developed, including direct charge injection via electrostatic gating, [222][223][224][225] charge donation from physically or chemically adsorbed molecules or ions, [226][227][228][229][230][231] and covalent bonding 232,233 via edge functionalization or substituted atoms. [4][5][6][7][8][234][235][236][237][238] These doping methods impact the optical, electrical, and optoelectronic properties of 2D TMDs. For examples, physisorbed or chemisorbed molecules on 2D layers act as molecular gates by injecting charge, which can modulate PL intensity through different charge carrier polarity.…”
Section: Doping and Alloyingmentioning
confidence: 99%
“…As a result, a number of successful strategies for doping 2D materials have been developed, including direct charge injection via electrostatic gating, [222][223][224][225] charge donation from physically or chemically adsorbed molecules or ions, [226][227][228][229][230][231] and covalent bonding 232,233 via edge functionalization or substituted atoms. [4][5][6][7][8][234][235][236][237][238] These doping methods impact the optical, electrical, and optoelectronic properties of 2D TMDs. For examples, physisorbed or chemisorbed molecules on 2D layers act as molecular gates by injecting charge, which can modulate PL intensity through different charge carrier polarity.…”
Section: Doping and Alloyingmentioning
confidence: 99%
“…As an impurity, Mo atoms are well studied and cause bandgap narrowing through the substitution of W sites in monolayer WS 2 . 14,15,23,24) However, there are very few studies on the doping of other transition metals for monolayer TMDCs. In the present study, Nb is selected because its atomic size is comparable to that of Mo and it is reported to generate acceptor states for some TMDCs.…”
mentioning
confidence: 99%
“…These results are similar WS 2 growth by halide-assisted CVD reported previously. 21) For structural characterization, we conducted annular dark field (ADF)-STEM observations of a monolayer sample 13,14,23) It should be noted that the STEM images of the doped samples are different from those of pure WS 2 monolayers as observed previously. 14) Through a statistical analysis of the ADF-STEM images obtained at six different positions of the same grain, the ratio of dark spots is estimated to be 0.55 ± 0.03%.…”
mentioning
confidence: 99%
“…Clean and sharp lateral interfaces in TMD HSs were reported in 2014 by three groups [30,31,32], improving on previous alloy growth M (1) X (1) x − M (2) X (2) 1−x [51,52,53,54,55,56,57] with different metal M (j) and chalcogen X (j) combinations. Recent experiments have shown successful growth of longer interfacial sections with great strain, geometry, and/or electronic band alignment tunability [37,38,36].…”
Section: Methodsmentioning
confidence: 76%